Analysis of a Pharmaceutical Company in The Current Economic Life - Petruţa MIHAI; Oana VLĂDUŢ; Ana-Magdalena ANGHEL; Mihaela-Florentina DUŢU; Iulian-Claudiu DUŢU; Maria-Valia MIHAI (Communications of International Proceedings, 2022)
The article herein features an analysis of the pharmaceutical company in terms of two main dimensions, theoretical and practical. The theoretical perspective illustrates the general notions about the organization X, while the practical one brings to the foreground the breakdown of the processes and services within the organization X and how they are performed, with a focus on the company strengths. The paper tries to find the ways and solutions through which a pharmaceutical company can develop in the existing situation in the Romanian economy, as well as in the health situation that the entire population of the world faces.
Keywords: processes; services; organization; pharmaceutical industry.